(untitled) (Baltic Journal of Sport and Health Sciences, 2015)
Background. The paper strives to answer the question what is optimism expression for middle school age students in physical education classes. The following hypothesis was tested: optimism expression of boys would be higher than those of girls. The aim of our study was to examine the optimism expression for middle school age students in physical education classes. Methods. The independent random sample consisted of 214 students of middle school age (108 girls and 106 boys). According to the attendance of physical education classes respondents by were divided into two groups: those who did not attend physical education classes for one month or more were assigned to the group of students not attending physical education classes, and others – the group of students attending physical education classes. The measure of optimism expression was evaluated using Dember’s Optimism/Pessimism Scale. Results. The hypothesis that optimism expression of boys would be higher than that of girls was confirmed. The comparison of optimism expression between boys and girls revealed that optimism expression for boys of middle school age was higher (p < .05) than that of girls. The comparison of optimism expression among students attending and not attending physical education classes revealed that middle school age students (boys, girls) attending physical education classes were more optimistic (p < .05). Conclusions. It was found that the optimism of middle school age boys was higher in physical education classes comparing them to girls of the same age, and middle school age students (boys and girls) who attended physical education classes were more optimistic. Keywords: physical education classes, the optimism expression, middle school age